Towards contemporary criminology - Ordaz Hernández, David (2017)
The authors analyze the challenge faced by criminology in the present century, marked by political, social and economic transformations, which constitutes a space of great theoretical challenges that can not be ignored. New criminal misconduct needs to be observed and understood to reorient objectives in criminological politics. They aim to determine if the theoretical and methodological systems of specific criminologies adequately explain the contemporary dynamics of crime and criminal justice, in order to determine if criminology needs adjustments to face a new reality.